2022
DOI: 10.1111/1753-0407.13289
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive risk profiles of family history and lifestyle and metabolic risk factors in relation to diabetes: A prospective cohort study

Abstract: Background Family history of diabetes, unhealthy lifestyles, and metabolic disorders are individually associated with higher risk of diabetes, but how different combinations of the three risk categories are associated with incident diabetes remains unclear. We aimed to estimate the associations of comprehensive risk profiles of family history and lifestyle and metabolic risk factors with diabetes risk. Methods This study included 5290 participants without diabetes at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Hypertriglyceridemia is becoming the most common form of hyperlipidemia, and increases the risks of acute pancreatitis, atherosclerotic cardiovascular disease (ASCVD), non-alcoholic fatty liver (NAFLD), and diabetes (Simha, 2020;Hernandez et al, 2021). The ensuing 60 years of research has indicated that there was a close correlation between hypertriglyceridemia and Type 2 diabetes mellitus (T2DM), which hypertriglyceridemia often existed years before the prediabetic and diabetic state (Berkowitz, 1966;Lorenzo et al, 2013;Li et al, 2020;Ye et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertriglyceridemia is becoming the most common form of hyperlipidemia, and increases the risks of acute pancreatitis, atherosclerotic cardiovascular disease (ASCVD), non-alcoholic fatty liver (NAFLD), and diabetes (Simha, 2020;Hernandez et al, 2021). The ensuing 60 years of research has indicated that there was a close correlation between hypertriglyceridemia and Type 2 diabetes mellitus (T2DM), which hypertriglyceridemia often existed years before the prediabetic and diabetic state (Berkowitz, 1966;Lorenzo et al, 2013;Li et al, 2020;Ye et al, 2022).…”
Section: Introductionmentioning
confidence: 99%